Kıbrıs Ağzıyla İlgili İki Araştırma - Sultanzade, Vugar (Yesevi Üniversitesi, 2013)
[Abstract Not Available]
The file in this item is the publisher version (published version) of the article.
Keywords: Kıbrıs ağzı; Türkçe - Lehçeler; Kıbrıs Türkçesi; Şive